CRITICAL ANALYSIS OF MATERIAL AND ENERGY RECOVERY PROCESSES OF MUNICIPAL SOLID WASTE IN SATU MARE COUNTY - MANESES, Sandor; SOPORAN, Vasile Filip (Studia Universitatis Babeș-Bolyai Ambientum, 2018)
This study suggests the description and the analysis on the ways of material and energy recovery of municipal solid waste, emphasizing on the stream that cannot be integrated into the classical recycling flux. We refer to the waste of this kind that includes, in a degraded state, plastic, paper and textiles that cannot be recycled or recovered through the existing procedures. Among the principal’s targets of this study, we enumerate: the analysis of stored waste composition in the regional DOBA store and its recovery potential; the material, energetical and environmental value determination of waste with recovery potential; Critical analysis on material and energetical recovery procedure of municipal solid waste. The motivation of this study is determined by the increasing of the volume of wrapping waste, plastic, paper and wood and by the low level of recycling that leads to finding alternative solutions for depositing, especially for components that have no recycling solutions. For these components, we are looking for alternatives developing the concept of material value; energetical value and environmental value for public waste, witch in this structure are identified, with their history, as “unusefull components” of a specific management process of circular economy. In concrete manner, appreciations are made on the following procedures: the material recovery, after a quick processing, selection and chopping; waste can be integrated in different composite materials, that can be used later, in constructions or urban furniture manufacturing; the energetical recovery, by co incineration in technological processes or by transforming waste into refuse derived fuel. Waste composition and value realization is made for specific Satu Mare county area.